Talking about a revolution? Costly and costless signals and the role of innovativeness in equity crowdfunding. (4th March 2023) - Di Pietro, Francesca; Grilli, Luca; Masciarelli, Francesca
ABSTRACT: Uncertainty and information asymmetries in crowdfunding can be reduced via the quality signals project proponents send to potential supporters. Drawing on signaling theory, this study analyzes how costly signals—venture's statements about past achievements and results—and costless signals—venture's statements about future plans and goals—influence crowdfunding performance. The results of a multimethod study of 597 UK equity crowdfunding campaigns suggest that only costly signals increase the amount raised through crowdfunding and that costless signals generally have a negative effect. However, for companies introducing radical innovations use of costless signals is not punished by the crowd.